Oral squamous cell papilloma: a case report - ÖZTÜRK ÖZENER, HAFİZE; KURU, LEYLA (AVES PRESS LTD, 2015)
Oral squamous cell papilloma (OSCP) is a benign proliferation of the stratified squamous epithelium, which results in a papillary or verrucous exophytic mass. OSCP is usually associated with human papilloma virus. Although any surface of the oral cavity can be affected, the sites of predilection for localization of the lesions include the tongue, lip and soft palate. In this report, treatment and histological findings of a local gingival enlargement at the vestibular side of the upper right central tooth of a 10 year-old systemically healthy girl are presented. The lesion was asymptomatic and had shown a slow growth. Solitary, exophytic lesion was clinically soft, pink-white in color and appeared as cauliflower. Dental and periodontal tissues were radiographically normal. One month after scaling and root planing, under local anesthesia the lesion was excised and this was followed by the use of Nd: YAG laser (1064 nm, 20 Hz, 3 W) to control bleeding, minimize pain and scarring in post-operative period, and provide sterilization. Macroscopic examination revealed that the lesion was 1.1x0.5x0.2 cm(3) in size, yellow in colour and had a rough surface, while histological examination showed multi-layer connective tissue underlying the squamous epithelium, numerous rete pegs and spinous cell proliferation at the papillary and OSCP was diagnosed. There was no evidence of viral cytopathic effect or malignancy of the lesion. No recurrence was observed during the 4-year follow-up period..
Keywords: Histological examination; human papilloma virus; lasers; papilloma